Proposta metodológica para definição de rede cicloviária : um estudo de caso de Maringá - Neri, Thiago Botion (2012)
Cycling lanes can be effective ways to mitigate traffic problems caused by the excessive number of vehicles, and they contribute to increase life quality in cities and metropolitan areas. In recent decades, due to climatic changes and the possibility of the depletion of natural resources, such as minerals and oil, sustainability concepts are gaining strength, especially in developed countries. One of the fields in which this concept is developing faster is in the sustainable mobility, where alternatives for non-motorized modes of urban displacements are created, and the use and the occupancy are planned. In addition, there is also improvement in the public transportation, thus reducing the utilization of motorized individual modes. The search for cycling lanes alternatives is growing and excelling, especially in European cities, and more recently in the American continent. However, many Brazilian cities do not have a good infrastructure yet. Among several factors that influence the use of bicycles for transportation, we highlight cultural characteristics, climate, topography and implemented structure. In an urban transportation system, a bicycle may have complementary roles, providing support to other alternative modes, being used for small and large displacements. Hence, this work aims to organize and apply a method to verify the urban cycling lanes potential- firstly by observing the general cycling lane characteristics of the city, then by investigating the urban aspects and the potential highways, and finally, by analyzing the potential networks. Maringá is the object of this study. The methodological procedures developed for this purpose were based on other author's projects and research, and were divided into three stages. First, in a macro observation, the city was analyzed, being addressed aspects such as topography, climate, size, and the urban form, items in which Maringá achieved satisfactory results and are compatible with cycling transportation. Next, it was surveyed the areas and sites of potential attraction / generation of cycling dislocations, and then it was selected the potential urban highways that were analyzed and stood out with a very high potential, and which also achieved high standards considering technical feasibility parameters, adaptability and spatial quality, and environment. All the axes possessed satisfactory outcomes between medium and high potentials, which accredited them for the final research stage. In step three, in nets, the potential cycling lanes axes stood out for covering a large area of influence within the city limits, by forming a stretch of bicycle tracks connected to each other, and in their majority, interconnecting to modal terminals and future transportation corridors, seeking the bike connections to others urban transport systems. In this sense, the city of Maringa showed a very high cycling lane potential level, being possible to develop projects for bicycle transportation in all regions of the city, which may encourage the government to include this subject in future urban development plans.